A simple and efficient real-coded genetic algorithm for constrained optimization - Chuang, Yao-Chen; Chen, Chyi-Tsong; Hwang, Chyi (Applied soft computing, 2016)
•A novel and efficient RCGA for constrained optimization has been proposed.•The proposed RCGA integrates three effective and novel evolutionary operators named RS, DBX and DRM.•The proposed RCGA is proven to have a small complexity index and outperform many state-of-the-art algorithms.•The proposed RCGA has been successfully applied to optimize the GaAs film-growth performance of an MOCVD process. This paper presents a simple and efficient real-coded genetic algorithm (RCGA) for constrained real-parameter optimization. Different from some conventional RCGAs that operate evolutionary operators in a series framework, the proposed RCGA implements three specially designed evolutionary operators, named the ranking selection (RS), direction-based crossover (DBX), and the dynamic random mutation (DRM), to mimic a specific evolutionary process that has a parallel-structured inner loop. A variety of benchmark constrained optimization problems (COPs) are used to evaluate the effectiveness and the applicability of the proposed RCGA. Besides, some existing state-of-the-art optimization algorithms in the same category of the proposed algorithm are considered and utilized as a rigorous base of performance evaluation. Extensive comparison results reveal that the proposed RCGA is superior to most of the comparison algorithms in providing a much faster convergence speed as well as a better solution accuracy, especially for problems subject to stringent equality constraints. Finally, as a specific application, the proposed RCGA is applied to optimize the GaAs film growth of a horizontal metal-organic chemical vapor deposition reactor. Simulation studies have confirmed the superior performance of the proposed RCGA in solving COPs.